UNIVERSAL PRIMARY EDUCATION: PERSPECTIVES FROM UGANDA - Okware, Fabiano (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The study aimed at assessing the implementation, achievements, experiences and challenges of MDG 2 for UPEProgramme in Uganda. Opinions of key stakeholders were sought. The study revealed some significant successes inensuring access to free and compulsory education and in reducing gender disparities at the primary school level. Thegreatest challenge remains that of more girls than boys not completing the primary cycle. The lessons learnt are: politicalcommitment, government support, quality education to motivate learners to stay at school, motivation of teachers for theirhigh commitment and stakeholder involvement.